ANALISIS TEKANAN EKSTERNAL, KETIDAKEFEKTIFAN PENGAWASAN, DAN KARAKTERISTIK INDUSTRI DALAM MENDETEKSI KECURANGAN LAPORAN KEUANGAN - Sukiati , Wiwin; Marcela , Luisa; Gustirani, Indri; Dwijayanti , Rima (Jurnal SIKAP (Sistem Informasi, Keuangan, Auditing Dan Perpajakan), 2024)
This study aims to examine the influence of external pressure, ineffective monitoring, and industry conditions on financial statement fraud. The research utilizes secondary data in the form of annual financial reports of companies, which are accessible through the Indonesia Stock Exchange (IDX) website, covering the period from 2020 to 2022. The population consists of 79 manufacturing companies in the basic and chemical industry sector. The sampling method employed is purposive sampling, resulting in a final sample of 23 manufacturing companies in the basic and chemical industry sector listed on the Indonesia Stock Exchange. Financial statement fraud is measured using the Beneish M-Score, and the analytical technique applied is multiple linear regression. The analysis is conducted using EViews 12 software.